2018
DOI: 10.1016/j.jtcvs.2017.08.141
|View full text |Cite
|
Sign up to set email alerts
|

Favorable prognosis and high discrepancy of genetic features in surgical patients with multiple primary lung cancers

Abstract: A high discordance of driver mutations between tumors in individual patients and a favorable prognosis were identified in patients with multiple primary lung cancers diagnosed by clinical-pathologic criteria, which support different strategies from those with metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 25 publications
2
30
3
1
Order By: Relevance
“…There are also reports [11,16,17] in the literature that multiple GGO patients with surgical resection,the prognosis is satisfactory, even sub-lobectomy does not affect the prognosis. In view of the good prognosis of multiple GGOs [18][19][20], we suggest that sub-lobectomy should be performed as much as possible for patients with multiple GGOs in the same period of surgery, which can ensure the prognosis and make the patient better quality of life. However, according to the rapid pathological results of the operation, the best resection plan was adopted.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports [11,16,17] in the literature that multiple GGO patients with surgical resection,the prognosis is satisfactory, even sub-lobectomy does not affect the prognosis. In view of the good prognosis of multiple GGOs [18][19][20], we suggest that sub-lobectomy should be performed as much as possible for patients with multiple GGOs in the same period of surgery, which can ensure the prognosis and make the patient better quality of life. However, according to the rapid pathological results of the operation, the best resection plan was adopted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported that patients with at least 1 driver mutation had a high inconsistency rate of 80%. Recently, Chen et al 31 reported a high inconsistency rate (89.7%) in genetic alterations between tumors within individual patients. Liu et al 32 studied the genomic profiles of 15 LUAC, which showed different genomic profiles, indicating that they were independent primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite such tendencies in some individuals for neoplastic development, this has not necessarily correlated with a poorer prognosis, 8 consistent with findings produced by Chen and colleagues. 1 Interestingly, however, if the occurrence of multifocal disease in patients with multiple GGOs were related to a field effect, one would hypothesize that there would be greater concordance among the driver mutations of tumors within the same patient for those in group A. Nonetheless, this did not appear to be the case.…”
mentioning
confidence: 96%
“…colleagues 1 clearly showed that patients with multiple GGOs had better prognoses than did those with multiple solid nodules. In a somewhat unrelated but equally important outcome of interest, Chen and colleagues 1 also found a significant extent of discordance between genetic abnormalities when comparing tumors in a given individual patient (90%), suggesting that the secondary lesions developed as independent primary tumors rather than as intrapulmonary metastases.…”
mentioning
confidence: 99%
See 1 more Smart Citation